2016
DOI: 10.1089/scd.2016.0143
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the POU5F1 Homologue in Nile Tilapia: From Expression Pattern to Biological Activity

Abstract: POU5F1 (OCT4) is a crucial transcription factor for induction and maintenance of cellular pluripotency, as well as survival of germ cells in mammals. However, the homologues of POU5F1 in teleost fish, including zebrafish and medaka, now named Pou5f3, exhibit considerable differences in expression pattern and pluripotency-maintaining activity. To what extent the POU5F1 homologues are conserved in vertebrates has been unclear. In this study, we report that the POU5F1 homologue from the Nile tilapia (Oreochromis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…A role in germ cell survival and apoptosis was proposed: in agreement with the apoptosis‐induced sexual differentiation in the developing gonad (Rodriguez‐Mari et al, ). Yet, in adult teleosts, such as the Japanese flounder Paralichthys olivaceus (Temminck & Schlegel 1846), Medaka Oryzias latipes (Temminck & Schlegel 1846) and Nile tilapia Oreochromis niloticus (L. 1758), oct4 – pou5f3 was restricted to the gonad and, in P. olivaceus its expression was continuous throughout oogenesis, in agreement with the present results (Sanchez‐Sanchez et al, ; Xiaohuan et al, ; Gao et al, ). Similarly, the pluripotency and proliferation–differentiation modulator nanog , yielded no significant results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A role in germ cell survival and apoptosis was proposed: in agreement with the apoptosis‐induced sexual differentiation in the developing gonad (Rodriguez‐Mari et al, ). Yet, in adult teleosts, such as the Japanese flounder Paralichthys olivaceus (Temminck & Schlegel 1846), Medaka Oryzias latipes (Temminck & Schlegel 1846) and Nile tilapia Oreochromis niloticus (L. 1758), oct4 – pou5f3 was restricted to the gonad and, in P. olivaceus its expression was continuous throughout oogenesis, in agreement with the present results (Sanchez‐Sanchez et al, ; Xiaohuan et al, ; Gao et al, ). Similarly, the pluripotency and proliferation–differentiation modulator nanog , yielded no significant results.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to RA metabolism, the expression patterns of the egg yolk precursor vitellogenin vtg1 and of the pluripotency markers oct4 – pou5f3 and nanog were also determined. Oct4 – pou5f3 and nanog are homeodomain transcription factors which modulate pluripotency: while the former stimulates and maintains pluripotency and promotes survival of germ cells (Frankenberg & Renfree, ; Xiaohuan et al, ; Gao et al, ), the latter is linked to the acquisition of pluripotency, favouring proliferation instead of cellular differentiation (Camp et al, ; Theunissen et al, ; Schuff et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pou5f1 is an important marker gene of stem cells. In the past 20 years, the homologues of Pou5f1 in mammals as well as in other vertebrates, including human [ 34 ], bovine [ 35 ], brushtail possum [ 36 , 37 ], rhesus monkey [ 38 ], platypus [ 39 ], vole [ 40 ], chicken [ 41 ], xenopus [ 42 ], zebrafish [ 21 , 43 ], medaka [ 17 , 44 ], Chinese sturgeon [ 45 ], goldfish [ 18 ], and Nile tilapia [ 19 ], have been identified. Several research studies have revealed their critical roles during early embryonic development and their importance in the maintenance of stem cell pluripotency.…”
Section: Discussionmentioning
confidence: 99%
“…A specific expression of Oct4 among mouse adult tissues is observed in the germ stem cells [ 13 , 14 ]. In contrast to the ICM localization of Oct4 in mammals, the homologue of Oct4 in lower teleosts, which was recently renamed pou5f3 , is spatially expressed throughout the blastomere from fertilized egg to gastrulae [ 15 , 16 , 17 , 18 , 19 ]. In addition to pluripotency regulation, zebrafish pou5f3 (originally named pou2/spg) also has some new roles as well as partial function loss when compared with other species.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell maintenance and pluripotency may be important for sex change in wrasses, where no male germ cells are identifiable prior to sex change (Todd et al, 2019). Vertebrate pluripotency factor pou5f3 (POU domain, class 5, transcription factor 1) is critical for the maintenance and regulation of stem cell pluripotency in teleosts (Gao et al, 2017;Lacerda et al, 2019;Xiaohuan et al, 2016).…”
Section: Expression Of Major Sex Determination and Differentiation Genesmentioning
confidence: 99%